KELIMPAHAN BURUNG DI RESORT PEMERIHAN TAMAN NASIONAL BUKIT BARISAN SELATAN - Joana Dwi Wulandari; Sugeng Prayitno Harianto; Dian Iswandaru; Yulia Rahma Fitriana; Subki Subki (Jurnal Belantara, 2022)
The abundance of bird species in an area represents how conditions are in the area, such as the Pemerihan Resort, in Bukit Barisan Selatan National Park, as habitat for various wild bird species. The aim of research to analyze of abundance, diversity and conservation status of birds at the Pemerihan Resort. Data collection using the Point count method. The study recorded 76 bird species from 31 families with a total number of 1598 individuals. The highest relative abundance was the pacific swallow (Hirundo tahitica) with KR 23.59%, and the smallest abundance was the long-tailed shrike(Lanius schach), banded kingfisher (Lacedo pulchella), javan leafbird (Chloropsis cochinchinensis), red-bearded bee-eater (Nyctyornis amictus), red-billed malkoha (Phaenicophaeus javanicus), velvet-fronted nuthatch (Sitta frontalis), rufous piculet (Sasia abnormis), oriental dwarf-kingfisher (Ceyx erithacus), and indigo flycatcher (Eumyias indigo) 0.06%.  The higher the species abundance level indicates that the more diverse  species found. Many bird species found could benefit the management and the community around the Resort Pemerihan to protect these birds habitat. The data could benefit to implement sustainable use of the Resort, such as the development of birdwatching tourism by holding training guides for birdwatching by involving the community.